2014
DOI: 10.1038/srep03717
|View full text |Cite
|
Sign up to set email alerts
|

How dolphins see the world: A comparison with chimpanzees and humans

Abstract: Bottlenose dolphins use auditory (or echoic) information to recognise their environments, and many studies have described their echolocation perception abilities. However, relatively few systematic studies have examined their visual perception. We tested dolphins on a visual-matching task using two-dimensional geometric forms including various features. Based on error patterns, we used multidimensional scaling to analyse perceptual similarities among stimuli. In addition to dolphins, we conducted comparable te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 41 publications
2
21
0
Order By: Relevance
“…There were three distinct perceptual categories for the horses: shapes with curvature, shapes made of only vertical and horizontal lines, and shapes including diagonal lines. Figure 2c depicts the MDS results of previous studies [9]…”
Section: (B) Shape Discriminationmentioning
confidence: 98%
See 3 more Smart Citations
“…There were three distinct perceptual categories for the horses: shapes with curvature, shapes made of only vertical and horizontal lines, and shapes including diagonal lines. Figure 2c depicts the MDS results of previous studies [9]…”
Section: (B) Shape Discriminationmentioning
confidence: 98%
“…Three chimpanzees (Pan troglodytes) participated in previous experiments [9]. The chimpanzees lived with a social group of 13 individuals (including themselves) indoors and in an environmentally enriched outdoor compound (770 m 2 ) at the Primate Research Institute at Kyoto University (KUPRI) in Japan [10].…”
Section: (A) Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Tested in a visual-matching task, the patterns of perceptual similarities for two-dimensional forms of dolphins was found to be similar to those of chimpanzees and humans (Tomonaga et al, 2014). Contrarily to the previously mentioned hypothesis of color blindness in dolphins (Peichl et al, 2001), a behavioral experiment showed that a bottlenose dolphin had two peaks in spectral sensitivity and that it could discriminate between two wavelengths with equal brightness (Griebel and Schmid, 2002).…”
Section: Behavioral Data On Visionmentioning
confidence: 99%